The analysis of factors that effect business development and income of MSMEs in Denpasar city - Prawira D., I.B. Hendra; Dewi, Heny Urmila (International research journal of management, IT and social sciences, 2019)
The population in this study were all MSMEs players in the city of Denpasar, amounting to 30,840 MSMEs and the number of samples used as many as 100 MSME actors with a method of determining stratified proportional sampling. The data analysis technique used is path analysis. The results of the analysis show that: 1) capital, labor, and social capital have a positive and significant effect on the development of MSMEs in Denpasar City. This means that the availability of capital, the working hours of MSME actors and the application of the three dimensions of social capital namely trust, social norms, and social networks are very influential on the development of the MSME business sector. 2) Capital, labor, social capital, and business development have a positive and significant effect on the income of SMEs in Denpasar City. This means that capital ownership, labor, social capital and the development of MSMEs will have a positive and significant impact on increasing the income of MSME players. 3) Business development is a variable that mediates the influence of capital, labor and social capital on the income of SMEs in Denpasar City.